HIGH FLOW PRIAPISM IN 7 YEARS-OLD BOY AFTER ACCIDENTALLY CONSUMING APHRODISIAC CHOCOLATE: A CASE REPORT - Samudra, Fathan Satria; Seputra, Kurnia Penta; Daryanto, Besut; Nurhadi, Pradana (Indonesian Urological Association, 2023)
ABSTRACT Objective: This case report aimed to present our experience of conservative treatments for High Flow Priapism in children. Case(s) Report: A 7 years old boy presented with persistent and painless erections without sexual stimulation for 24 hours, the erection was first noticed when he woke up in the morning after accidentally consuming aphrodisiac chocolate 2 days before admitted to the hospital. There was no previous history of priapism and trauma or other risk factors. Discussion: Laboratory studies were within normal limits. Physical examination revealed a fully erect, nontender penile with rigid corpora cavernosa, soft glans, and erection hardness scale (EHS) 3. A cavernosal blood gas analysis was collected with the following values PH 7.41, pO2 117,7 mmHg, and pCO2 24, 8 mmHg. With diagnosis of High Flow Priapism, he was observed and got conservative treatments; ice and site-specific compression and after that EHS become 1. On follow-up after 2 months reported that patient had normal erections with no further episodes of priapism. Conclusion: High flow priapism in old boy after accidentally consuming aphrodisiac chocolate can managed by conservative therapy with favourable outcome. Keywords: Aphrodisiac chocolate, penile erection, priapism.